Analisis Sertifikasi Halal Tape Singkong untuk Meningkatkan Pemasaran UMKM Kuliner di Kampung Tape Desa Candi Binangun Kecamatan Sukorejo Kabupaten Pasuruan - Nola Rahmah; Sukamto; Aslikhah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This Halal certification is the process of obtaining halal certification through several levels of inspection to prove that the raw materials, manufacturing processes, and halal product assurance system of a company meet the established standards. Halal certification guarantees the benefit and well-being of the community. This research aims to examine the importance of halal certification in improving the marketing of culinary Micro, Small, and Medium Enterprises (MSMEs) and the impact of marketing MSME products after being certified halal, specifically cassava tape, in Kampung Tape, Candi Binangun Village, Sukorejo, Pasuruan Regency.The research method used is descriptive qualitative with data collection techniques through surveys, interviews, and observations. The results showed that halal certification plays an important role in increasing consumer confidence and opening up new market opportunities for MSMEs. The halal certification process is relatively easy to do online and free of charge, with support from the village government. After halal certification, cassava tape marketing experienced an increase in turnover and product attractiveness. MSME actors consistently use halal-certified raw materials to support business growth. Thus, halal certification has a positive impact on improving the marketing of culinary MSMEs in Kampung Tape, expanding market share, and increasing product competitiveness in the halal food and beverage industry.